2019
DOI: 10.1136/vetreccr-2019-000919
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lateral patellar luxation in a calf

Abstract: This case report documents the surgical treatment of bilateral lateral patellar luxation in a calf and the outcome by clinical examination, radiography, CT and postmortem examination. A 21-day-old calf was referred because of severe hindlimb weakness. Orthopaedic examination and radiographs revealed a grade 3 bilateral lateral patellar luxation with normal stifle bone anatomy. Surgery consisted of lateral desmotomy with excision of proliferative capsular tissues and imbrication of the medial retinaculum and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It has been reported that recurrence (%35) is the most common complication of LPL in dogs (15). However, in calf the main complications are wound infection and grade 2 dislocation (1). In our case, we did not encounter any complication following the postoperative six weeks.…”
Section: Discussionsupporting
confidence: 41%
See 4 more Smart Citations
“…It has been reported that recurrence (%35) is the most common complication of LPL in dogs (15). However, in calf the main complications are wound infection and grade 2 dislocation (1). In our case, we did not encounter any complication following the postoperative six weeks.…”
Section: Discussionsupporting
confidence: 41%
“…Patellar luxations have been reported in various species including dog (8), llamas (9), rabbit (10), (11), foal (12), and horse (13). The etiological reasons of patella dislocations are classified as congenital, traumatic, and developmental (1). Traumatic patella luxation is generally observed in large animals and mostly they are congenital (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations